Evaluasi Perbandingann Kinerja Reksa Dana Saham, Portofolio yang Disusun Secara Random, dan indeks-Indeks yang Tercatat di Bursa Efek Indonesia - , Awaluddin Asa'ad ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Equity fund is a portfolio of stocks that are professionally managed by an investment manager who is one of the preferred investment instruments for investors. Investors who have limitations in shaping their own portfolios entrusted entirely to investment managers in the management of its capital in the form of equity funds. This study aims to evaluate and compare the performance of an equity fund managed by the investment manager to the performance benchmark consisting of randomly arranged portfolios and listed index in Indonesia Stock Exchange. The performance evaluation is done by using the Sharpe, Treynor, and Jensen's alpha measurement. In the evaluation and performance analysis also tests the average difference and significance test to determine whether or not there are differences in performance. The samples in this study were 30 mutual fund shares to be evaluated, each of 30 random portfolios consisting of 5, 10, and 15 stocks and 9 listed index in the Indonesia Stock Exchange as a comparison. This study uses monthly data NAB equity funds, individual stock prices, the index, and the BI rate in the period July 2010 to July 2012. The results of this study indicate that based on the measurement of the performance of Sharpe, the performance of equity funds is no different or better than the performance of a portfolio of randomly drawn 5, 10, and 15 stocks, and the performance of the index. According to Treynor performance measurement, the result that the performance of mutual fund shares just better than random 10 stocks portfolio performance, but performance has not different or no better than random portfolio 5 and 15 stocks, and performance index. Based on Jensen performance measurement result that the performance of mutual funds share proved no different or can not be beat either arranged randomly composed portfolio of 5.10, and 15 stocks and no better than the performance of the index anyway.